Hubungan Latihan Fisik dan Pola Makan dengan Kejadian Reumatoid Artritis (Ra) pada Lansia di Panti Sosial Tresna Werdha Minaula Kendari Tahun 2017 - Narmi, Narmi; S, Evi (Jurnal Gizi Ilmiah, 2017)
Rheumatoid arthritis is a chronic systemic inflammatory disease with the main manifestation of progressive polyarthritis and involving all organs of the body. Rheumatoid Arthritis (RA) is caused by factors such as physical exercise and diet. This study aims to determine the relationship between physical exercise and diet with the incidence of Rheumatoid Arthritis (RA) in the elderly. This research is a descriptive analytic study with a Cross Sectional Study design and was carried out on March 29 - April 4 at the Tresna Werdah Social Home, Minaula Kendari 2017. The sampling technique with a total sampling of 55 elderly respondents suffering from Rheumatoid Arthritis (RA), the instrument research using a questionnaire. The research analysis used the Kolmogorov Smirnov test statistical test. The results showed that 9 people (16.4%) elderly with light physical exercise experienced severe rheumatoid arthritis and a small proportion, namely 5 people (9.1%) elderly who did heavy physical exercise, experienced mild rheumatoid arthritis, mostly 8 people (5 ,5%) elderly have adequate diet, experience severe rheumatoid arthritis and a small proportion of elderly with good diet experience mild rheumatoid arthritis incidence, namely 5 (9.1%). The conclusion is that the p value (0.04) < (0.05), which means that the alternative hypothesis is accepted and the null hypothesis is rejected, so that there is a relationship between physical exercise and the incidence of Rheumatoid Arthritis, the p value (0.03) < ( 0.05), which means that the alternative hypothesis is accepted and the null hypothesis is rejected, so there is a relationship between diet and the incidence of rheumatoid arthritis. Suggestions in this study are expected for the orphanage to establish policies in optimizing prevention and treatment programs to minimize rheumatoid arthritis from mild to severe, as well as different types of food between elderly people with rheumatoid arthritis to avoid foods that trigger the worsening of rheumatoid arthritis.